Effect of Oral Ibuprofen and Oral Acetaminophen in the Treatment of Symptomatic Patient Ductus Arteriosus in Premature Infants - Ahlawat, Kuldeep Singh (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Patency of the ductus arteriosus (PDA) is a prevalent condition in preterm neonates with respiratory distress syndrome (RDS), and 60 percent to 70 percent of preterm children born at 28 weeks have PDA treatment, either medically or surgically. Subjects and Methods: All preterm children delivered at Career Institute of Medical Sciences & Hospital with a PDA and a diagnostic age of less than 14 days were included in the study. All preterm children were checked for oxygen dependency; increased PCO2, heart murmur, heart failure symptoms, Bounding Pulse, and suspicion of PDA, echocardiography was performed on them. They enrolled in the trial if the condition was confirmed. After gaining parental consent, a total of 56 children with PDA were enrolled in the trial and were randomly assigned to one of two groups. Result: The ductus arteriosus was entirely closed in all 5 infants treated with acetaminophen and 5 of the 7 infants treated with ibuprofen who received the second round of treatment (P=0.12). According to the findings, there was no statistically significant difference between the side effects of the two prescription drugs, acetaminophen and ibuprofen (P=0.36). Conclusion: Oral Ibuprofen can effectively seal PDA, but it is regrettably linked with some side effects, limiting its utility. As a result, we investigated an alternate medicine with similar efficacy, less side effects, and fewer contraindications. Because Ibuprofen and Acetaminophen have similar efficacy and Acetaminophen has a higher safety profile, it is recommended that Acetaminophen be used first.